Parent and Family Functioning in Pediatric Inflammatory Bowel Disease - Grace Cushman; Sharon Shih; Bonney Reed (MDPI AG, 2020)
Although the impact of pediatric inflammatory bowel disease (IBD) extends beyond the patient to their parents and families, the focus of previous literature has largely been on investigating the patient's medical and psychosocial functioning, with less consideration of the family system. Having a comprehensive understanding of parent and family functioning within the context of pediatric IBD is important given the role parents and family members have in the successful management of the disease and caring of the child. The current review paper aggregates the empirical research regarding parent and family functioning, including comparisons to normative samples, other illness groups, and how functioning relates to child psychosocial and health outcomes. Extant literature on parents and families in pediatric IBD has largely focused on the variables of parenting stress, parent psychosocial functioning, parent quality of life, and family functioning. Summary findings elucidate the complex relationships between parents, families, and children affected by IBD and highlight the importance of assessing parent and family functioning within pediatric IBD. The current review also offers implications for clinical practice, notes the limitations of the present literature, and provides recommendations for future research.